Fatores maternos e fetais associados ao insucesso da indução por misoprostol em gestações a termo: uma revisão integrativa - Brito, Juliana Oliveira (2022)
The induction consists of the use of methods mechanical or pharmacological means to trigger labor, in pregnant women with an indication of resolution of the pregnancy through vaginal delivery. The pharmacological method addressed in this work is misoprostol, a synthetic prostaglandin of the E1 type, prescribed by the doctor, which has a uterotonic action, modifying the cervix, favoring its softening, distensibility, with subsequent effacement and dilation. An obstetric conduct that collaborates with the reduction of the high rate of unnecessary cesarean sections, which is peculiar to the Brazilian reality. Taking into account the outcomes of unsuccessful induced labor, the incidence of cesarean sections and the existing gap in the literature due to the lack of studies that analyze the pre-induction factors that may interfere in the process, this study is justified by its contribution to strengthening of the safe practice of health professionals who work in maternal-fetal care, supporting them in choosing the best conduct to resolve each pregnancy individually, predicting and avoiding negative outcomes. The objective was to analyze which maternal and fetal factors are associated with failure of misoprostol induction in term pregnancies. This is an integrative literature review through a search in the MEDLINE databases; Web of Science; CINAHL; EMBASE and Scopus. Access to the articles was through the journal portal of the Coordination for the Improvement of Higher Education Personnel (CAPES), through national and international exchanges, and through partnership with nurses at Langara College in British Columbia - Canada. The guiding question was: what maternal and fetal factors are associated with failure of misoprostol induction in term pregnancies? Original studies were selected that described the percentage of failure associated with the use of misoprostol alone or in comparison with another intervention, either as a primary or secondary outcome, without time and language restrictions. The search and evaluation of the articles was carried out by two researchers, independently, from January to May 2022, with the help of the Endnote X7 reference manager. For the selection and identification phase of the studies, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was used. After the selection process and application of the inclusion and exclusion criteria of the studies, 11 articles were used to compose the review. The variables of interest for data collection were: failure rate, maternal and/or neonatal factors associated with failure. All documents included were in English and the period of publication ranged from 2000 to 2021, most studies were concentrated between 2013 and 2019, the country with the most publications was the United States of America, with three articles. All included studies have an observational design, longitudinal follow-up, five with prospective direction and six retrospective. The level of evidence of all articles, according to Oxford recommendations is 2b. The risk of bias was concentrated between 6 and 8, where 9 is the maximum classification in terms of quality, according to the Newcastle Ottawa Scale, suitable for observational studies. Maternal and/or neonatal factors associated with induction failure were, respectively: high BMI (greater than 30kg/m2), nulliparity, immature bishop (less than 5), cervical length (greater than 30mm), height (166.3 ± 6.6, p=0.001), ethnicity (non-Caucasians from Southern Europe) and fetal weight (greater than 4kg). Within a clinical context, analyzing the risk of labor induction failure can bring benefits to care, as well as optimization of resources, being the basis for selecting the best induction method, effective dose and application interval for each pregnant woman in her individuality.